Avian fruit colour preference in UiTM Negeri Sembilan Campus Kuala Pilah / Nurul Nadiah Mohd Azme - Mohd Azme, Nurul Nadiah (Faculty of Applied Sciences, 2015)
Colour plays as major factor to determine fruit colour selection and the artificial fruit pattern to identify the fruit display pattern preferred by avian because avian have excellent vision acuity and well developed colour vision that being use in foraging for food. Colour is a key characteristic of fruits because it affects the probability that they will be noticed or selected. Fruit colour explained the preferences of fruit that choose by avian species. A paired experimental design isolated and grouped fruit pattern was used to establish these studies. The plasticine was moulded 300 artificial fruits with 14 mm diameter spherical in three different colours, red, yellow and dark purple. Avian may learn to ignore such differences while foraging. Red is one of the most common colours of avian to dispersed fruits. Avian colours preference has an effect on the fruits perceived and eaten. Seed dispersal by animals is an important mutualistic interaction between fleshy-fruited plants and avian. From results by using “chi-square” shows that red are the most preferences 54.8% followed by yellow 29.5% and dark purple 15.8% and for display pattern it shows that isolated are more preferences 65.1% compared to grouped 34.9%.